A k-Nearest Neighbor Based Algorithm for Human Arm Movements Recognition Using EMG Signals - MIEEE, Mohammed Z. Al-Faiz; A.Ali, Abduladhem; Miry, Abbas H. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
In a human-robot interface, the prediction of motion, which is based on context information of a task, has the potential to improve the robustness and reliability of motion classification to control human-assisting manipulators. The objective of this work is to achieve better classification with multiple parameters using K-Nearest Neighbor (K-NN) for different movements of a prosthetic arm. The proposed structure is simulated using MATLAB Ver. R2009a, and satisfied results are obtained by comparing with the conventional recognition method using Artificial Neural Network (ANN). Results show the proposed K-NN technique achieved a uniformly good performance with respect to ANN in terms of time, which is important in recognition systems, and better accuracy in recognition when applied to lower Signal-to-Noise Ratio (SNR) signals.